Small mammals in a fragment and adjacent matrix in southeastern Brazil - Passamani,M. (2009)
Between May 2002 and May 2003, we studied a small mammal community from an Atlantic forest fragment surrounded by a coffee plantation in the municipality of Santa Teresa, Espírito Santo state, Brazil. We obtained a total of 300 captures of 114 individuals belonging to 11 mammal species. Seventy three percent of the species captured in the forest also used the coffee plantation, mainly males (90%) and young (80%) individuals of Marmosops incanus. The exceptionally low recapture rate in the coffee plantation suggests that it functions as a corridor between fragments, rather than as a habitat for these species. Understanding the role of matrix habitat use in fragmented landscapes is an important factor in small mammal conservation, as it asymmetrically affects the rate and mode of individual movements of different species.